Trend in basic oral treatment needs in relation to taxation of sweets, ice cream, and sugar-sweetened beverages in Finland: a registry-based study - Jesse Jokirinta; Jari Päkkilä; Evangelos Mourelatos; Sakari Sipola; Marja-Liisa Laitala; Saujanya Karki (Medical Journals Sweden, 2024)
Objective: The aims were to explore the trend in basic oral treatment needs and total operating cost of public dental services (PDS) in relation to total excise tax revenue generated from sugary products during 2011-2020 and to evaluate the impact of tax policy in excise tax revenue of sugary products and average sugar consumption. Methods: The study comprised longitudinal data retrieved from Finnish registries during the years 2011-2020. Basic oral treatment needs, and total operating cost of PDS, total excise tax revenue generated from sugary products and average sugar consumed (kg per capita) during the years 2011-2020 were obtained. Simplified panel analyses and sensitivity analyses were used to evaluate the effects of explanatory variables on outcomes.  Results: An approximate one EUR 1,000,000 increase in total excise tax revenue generated from sugary products corresponds to a 0.4% increase in total operating cost of PDS. There was a significant positive trend in total operating cost of PDS in Finland over the study period. Similarly, an approximate one EUR 1,000,000 rise in total excise tax revenue corresponds to a 0.2% increase in basic oral treatment needs. Additionally, there was a statistically significant difference in the average excise tax revenue for sugary products between the periods before and after 2017. Conclusion: No change in average sugar consumption was observed despite implementing the new sugar policy. Therefore, it may be worthwhile to reconsider the excise tax on sweets and ice cream as it will significantly increase the total national revenues.